A novel medical protocol to treat uterotubal spasm during Essure hysteroscopic sterilization: a pilot study - Chapa HO; Venegas G (Dove Medical Press, 2012)
Hector O Chapa,1 Gonzalo Venegas21Women's Specialty Center, Dallas, TX, USA; 2Clinical Faculty, Department ObGyn Methodist Medical Center, Dallas, TX, USAObjective: To evaluate sublingual hyoscyamine (0.125 mg) as a uterotubal spasm reliever to increase successful bilateral, first-attempt Essure microinsert placement.Study design: Prospective cohort study as pilot clinical investigation of study medicine.Setting: An inner-city Dallas, TX obstetrics and gynecology office practice.Materials and methods: The study period was January 1, 2008 to July 1, 2010. Patients requesting sterilization were offered Essure under local anesthesia (office setting). Those declining were referred for operative laparoscopy. Patients accepting office sterilization were offered study participation. Study patients noted to have intraoperative uni/bilateral uterotubal spasms preventing cannulation were given one sublingual hyoscyamine (0.125 mg) tablet. Primary endpoint: spasm alleviation and successful tubal cannulation (bilaterally). Secondary endpoint: percentage of bilateral tubal occlusions documented by follow up hysterosalpingogram (12 weeks), and adverse events possibly related to medication.Results: Within the study period, 316 patients underwent office sterilization (local anesthesia); 21 had unilateral tubal spasm preventing cannulation (6%). Spasm was relieved in 17/21 (80%) after hyoscyamine, allowing for microinsert placement. The mean time from attempted cannulation to medication was 9 minutes (8.3–10.5 minutes), and the mean time for spasm resolution was 53 seconds (49–72 seconds). At follow-up confirmation testing, all 17 who were hyoscynamine responders were found to have bilateral tubal occlusion as well as proper microinsert location. The 4/21 hyoscyamine nonresponders underwent a second unilateral attempt 48–72 hours later. Fifty percent (n = 2) had successful placement, leaving two for alternative care. Rapid pulse was reported by 1/21 (4.7%) 5 minutes postmedication.Conclusion: Essure sterilization has a high bilateral, first-attempt success rate. Hyoscyamine may aid in spasm relief and increase single procedure, bilateral placement success rate further.Keywords: hysteroscopic sterilization, Essure, tubal spasm, hyoscyamine